Evidence for the involvement of ZNF804A in cognitive processes of relevance to reading and spelling - Becker, Jessica; Brandeis, Daniel (Translational Psychiatry, 2012)
Previous studies have shown that individuals with schizophrenia and dyslexia display common neurocognitive abnormalities. The aim of the present study was to determine whether known schizophrenia-risk genes contribute to dyslexia risk or to disease-relevant cognitive functions. For this purpose, we genotyped the schizophrenia-associated risk variants within zinc-finger protein 804A (ZNF804A), transcription-factor 4 and neurogranin in a large dyslexia case-control sample. We tested all variants for association with dyslexia (927 cases, 1096 controls), and with eight language-relevant cognitive processes (1552 individuals). We observed six significant associations between language-relevant traits and the ZNF804A-variant rs1344706. Interestingly, the ZNF804A schizophrenia risk variant was associated with a better cognitive performance in our data set. This finding might be consistent with a previously reported ZNF804A association in schizophrenia, in which patients carrying the schizophrenia-risk allele at rs1344706 showed a better performance in two memory tests. In conclusion, the present study provides evidence that ZNF804A might have a role in cognitive traits of relevance to reading and spelling, and underlines the phenotypic complexity that might be associated with ZNF804A.